Modification of Tyre Rubber Crumb with Wastes of Plant Oil Production - Guzaliya Faritovna Sagitova; Galiya Nyssanovna Kalmatayeva; Saule Abdrazakovna Sakibayeva; Dina Duisenbekkyzy Assylbekova; Ainur Slambekovna Sadyrbayeva; Zhuldyz Kenzhebayevna Shukhanova (Advances in Polymer Technology)
Recovery of fat-and-oil production wastes will reduce the technogenic impact on the environment, as well as involve them in a new production cycle as a secondary material resource. As part of solving this problem, the possibilities of using fat-and-oil production wastes in the production of a tyre reclaim and a modified tyre reclaim are considered. In the course of the studies, the fat-and-oil industry wastes’ sorption characteristics are determined, and in relation to oils in static and dynamic conditions, the spent reagent reclamation ways are determined. The authors obtained a tyre reclaim and a modified tyre reclaim using the fat-and-oil industry wastes (soap stock, diatomite, bleaching clay, and fatty acids isolated from soap stock). In this work, the authors studied the possibility of using the fat-and-oil industry wastes in the formulations of a tyre reclaim and a modified tyre reclaim. Extended physical and mechanical tests of experimental rubbers led to the conclusion that it is most expedient to use the fat-and-oil industry wastes in the formulation of rubber compounds for production of sleeper pads for railroad tracks, since when using a tyre reclaim and a modified tyre reclaim, the indicators of rubber properties practically do not change and comply with control standards.